SOCIAL MEDIA AS A UNIFYING OR DIVIDING TOOL? A SOCIOLOGICAL ANALYSIS - Ahmad Taufiq; Lenny Dawati Sinaga; Roni Sugiarto (ADISAM Publisher, 2025)
In the digital era, social media has become one of the main components in the life of the global community. This article analyses the role of social media from a sociological perspective, with the aim of understanding whether social media serves more as a unifying or dividing tool for communities. On the one hand, social media has the ability to bring together individuals from different parts of the world, form solid communities based on shared interests and values, and facilitate social mobilisation and solidarity campaigns. On the other hand, it can also deepen social polarisation and fragmentation through algorithms that create echo chambers, as well as the spread of disinformation and hateful content that fuels social conflict. Thus, social media is a double-edged sword that requires critical understanding and appropriate policies to maximise its potential as a unifying tool, while reducing its risk as a divisive tool.